Pengaruh Penyajian Laporan Keuangan Dan Aksesibilitas Laporan Keuangan Terhadap Akuntanbilitas Pengelolaan Keuangan Desa - Hambali, Deni; Rizqi, Reza Muhammad (Politeknik Raflesia Press, 2024)
This research aims to determine the influence of the presentation of financial reports and the accessibility of financial reports on the accountability of village financial management. The sample in this research was village officials or officials in Utan District, Sumbawa Regency, totaling 9 villages with a total sample of 45 respondents. The research results show that the presentation of financial reports influences the accountability of village financial management and the accessibility of financial reports influences the accountability of village financial management. Then, simultaneously presenting financial reports and accessibility of financial reports, influences the accountability of village financial management in Utan District, Sumbawa Regency. In conclusion, accountability in managing village money is an important part of carrying out good village governance. This is necessary to ensure that village funds are used clearly, effectively and efficiently, as well as improving the standard of living of the people in the village.